The impact of global value chain embedding on the upgrading of China’s manufacturing industry - Fu, Qingwei (Frontiers in Energy Research, 2023)
In the current international trade characterized by global value chains (GVCs), to improve the trade interests of China’s manufacturing industry and change the unfavorable situation of “big but not strong,” industrial upgrading is an important issue that needs to be solved urgently. Based on the analysis of the impact of embedding in GVCs on the acquisition of trade benefits, the paper empirically tests the impact of embedding GVCs on manufacture upgrading by using industry segmentation data of China’s manufacturing industry from the year 2000 to 2014 in the world input–output database. The research shows that 1) from 2000 to 2014, forward and backward participation increased from 11.2% and 15.2% to 14.6% and 15.9%, respectively; China’s manufacturing industry mainly participates in the GVC in a backward way, which significantly improves trade interests; 2) both forward participation and backward participation in the GVC are conducive to the increase of trade benefits and are positive at the 5% level, which has a significant driving effect on the upgrading of the manufacturing industry; and 3) heterogeneity testing shows that capital-intensive, technology-intensive, and high-tech industries gain significant trade benefits, and embedding GVCs is more conducive to upgrading. Therefore, integrating into the GVC at a higher level is the direction to promote the upgrading of China’s manufacturing industry.